Intravesical Gemcitabine versus Intravesical Bacillus Calmette–Guérin for the Treatment of Non-Muscle Invasive Bladder Cancer: An Evaluation of Efficacy and Toxicity - Prasanna, Thiru; Craft, Paul; Balasingam, Gayathri; Haxhimolla, Hodo; Pranavan, Ganes (Frontiers in Oncology, 2017)
Background Intravesical Bacillus Calmette–Guérin (BCG) remains the standard adjuvant treatment for non-muscle invasive bladder cancer (NMIBC) following transurethral resection; however, BCG failure and related toxicities are common. Objectives To compare the efficacy and toxicity of intravesical BCG and gemcitabine in the treatment of NMIBC. Methods Retrospective data were collected in the region of Canberra, Australia from January 2010 to December 2015. The survival cutoff was December 2016. Primary end point was disease-free survival (DFS) and secondary end point was toxicity. After optimal transurethral resection all patients received weekly intravesical BCG or gemcitabine for 6 weeks and maintenance treatment according to their risk. The recurrence was defined as histology proven tumor recurrence (any grade), or appearance of carcinoma in situ. Results One hundred and three patients were evaluable, 52 treated with BCG and 51 with gemcitabine with a median age of 77 and 78, and were mostly male. Approximately half of each received maintenance therapy. The groups were well balanced, apart from some difference in cancer risk groups. Twenty-one percent in the BCG group and 29% in the gemcitabine group had received prior BCG. Median follow up was 15.0 months. Median DFS was 19.6 months for BCG, whereas median DFS was not reached with gemcitabine. There was a trend toward improved DFS with gemcitabine in multivariate analysis, HR: 0.49 (95% CI: 0.22–1.06, p = 0.07). Adverse events were significantly less frequent with gemcitabine (7 versus 44%, p ≤ 0.05). There were four cases of systemic BCG infection. Conclusion Intravesical gemcitabine was associated with a trend toward better DFS with significantly lower toxicity when compared with BCG. Intravesical BCG remains the standard first-line adjuvant therapy; however, intravesical gemcitabine could be a reasonable alternative in cases where BCG is contraindicated and for patients who are intolerant or refractory to BCG. A prospective phase 3 trial is needed to confirm the benefits of gemcitabine over BCG.